Evaluation of Principal Leadership Style in Increasing Teachers' Teaching Motivation: CIPP Model Approach - Desi Nalurita Sari; Wahyudi Wahyudi; Sophia Tri Satyawati (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study evaluates the effectiveness of a school principal’s leadership style in boosting teacher motivation through the CIPP (Context, Input, Process, Product) evaluation model. Using qualitative evaluative methods, data were collected through triangulation techniques in the form of in-depth interviews, field observations, and documentation analysis. Participants in this study numbered five people, consisting of one principal, three subject teachers who each had a minimum of five years of teaching experience and were active in the learning community (Kombel), and one education staff (administrative staff) who was directly involved in managerial activities with the principal. This study was conducted at Pangudi Luhur Tuntang Junior High School, with the main focus on how the principal's leadership style contributes to increasing teacher teaching motivation through a contextual, input, process, and product approach as applied in the CIPP evaluation framework. The findings show that the principal understands teachers' motivational needs and aligns leadership with the school's vision and mission. Participatory leadership and support for professional growth are evident, though resource limitations persist. The principal actively fosters collaboration, such as through a learning community, although these efforts are challenged by limited time and staff. The outcomes include increased teacher motivation, creativity, and engagement in teaching activities. However, formal systems to evaluate motivation remain underdeveloped. Overall, the principal's leadership style is largely transformational and participatory, positively influencing teacher motivation. Nonetheless, improvements are needed in systematic support and program continuity. These insights may guide school leaders and policymakers in strengthening educational leadership and improving teaching quality.